The influence of the polishing duration on the surface roughness and gloss of nanohybrid composites using a blood cockle shell polishing paste - Farahanny, Wandania; Andryas, Ika; Batubara, Fitri Yunita; Yanti, Nevi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: The polishing procedure is an important stage in producing a successful restoration. Polishing involves the use of abrasive materials, and blood cockle shells contain these natural components, such as calcium carbonate, which can be used as a polishing paste. One of the factors that influences the polishing quality is the polishing duration. Purpose: This study evaluated the polishability of a nanohybrid composite using blood cockle shell polishing paste by measuring the surface roughness and gloss value, and by observing the surface qualities based on different polishing times. Methods: Ninety samples of maxillary premolars were immersed in artificial saliva in an incubator at 37°C for 24 h. A total of 45 samples were subjected to a profilometer to observe surface roughness, and the rest were subjected to a glossmeter to observe the composite resin gloss. These included blood cockle shell paste, Prisma Gloss polishing paste, and without paste for 30, 60, and 90 seconds. The data were statistically analyzed using repeated measures ANOVA and post hoc least significant difference (LSD). Results: It showed that the group of 90 seconds had the highest gloss and the lowest surface roughness in the blood cockle shells. The difference was statistically significant (p>0.05). The results of the surface roughness test of the blood cockle shells with a duration of 30 and 60 seconds were found to be not significant (p<0.05). Conclusion: There were significant differences by adding the polishing duration, which decreased the surface roughness and increased the surface gloss, in which the lowest roughness and highest glossiness was found with a polishing time of 90 seconds. The polishability of composite resin restorations in this study obtained the best gloss and smoothest surface results from the longest polishing time duration of 90 seconds with the blood cockle shell polishing paste.